The Behaviour of Half-Slabs and Hollow-Core Slab in Four-Edge Supported Conditions - Jakub Zając (MDPI AG, 2021)
In this study, qualitative tests were carried out to compare the behaviour of selected slabs exposed to short- and long-term loading. Full-scale models of the half-slab and hollow-core slab with dimensions of 6.30 m × 6.30 m, built of four different precast panels, were tested. The first two were semi-precast lattice girder slabs, the third semi-precast prestressed ribbed panels, and the last was composed of hollow-core panels. A common feature was the lack of joint reinforcement and the same modular width of 600 mm. The short-term load was applied sequentially in the first stage, and displacement was measured using an electronic method. In the second stage of long-term testing, the load was mainly applied to one part of the slab. Testing under short-term and long-term load allows determining the change in the performance of panel slabs over time. The panels maintained the ability of load redistribution based on their interaction despite the work of the longitudinal joints being only through the concrete cross-section. The behaviour of slabs with concrete topping shows more significant lateral interactions than elements connected only by shear key. Comparative calculations were made based on four computational models. Comparative analysis showed that the current design procedures lead to a safe but conservative estimation of the slab behaviour.